Strategi Fundraising BAZNAS Kabupaten Tebo dalam Meningkatkan Penghimpunan Dana Zakat, Infak dan Sedekah - Nelly Anisatul Qoriah; Resky Mulyandari; Khoirun Nissa; Indah Agustina; Rizky Mulyo Wibowo; Isamuddin (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This research is motivated by the lack of optimal collection of zakat, infaq, and alms in Tebo Regency, even though BAZNAS has a strategic role in managing the funds of the people for the equitable distribution of social welfare. The research aims to analyze the fundraising strategy implemented by BAZNAS Tebo Regency, identify the obstacles faced, and formulate efforts to increase ZIS fund collection. The method used is descriptive qualitative research with a location at the BAZNAS Service Office of Tebo Regency. Data were obtained through observation, interviews with field staff, and documentation, and then analyzed using Miles and Huberman's interactive model through data reduction, data presentation, and conclusion drawn. The results of the study show that fundraising is still dominated by direct approaches, cooperation with government agencies, and strengthening UPZ, while indirect approaches through digitization of services, program publications, and social media campaigns are not optimal. The main obstacles include low zakat literacy, limited access to information, and uneven use of digital media, so integrative, educational, and gradual strategies are needed to expand the muzakki base and increase the effectiveness of sustainable fundraising in semi-rural communities of Tebo Regency.